Impact of American Society of Anesthesiologists score on postoperative holmium enucleation of the prostate outcomes and complications. Issue 4 (22nd November 2022) - Soyster, Mary E.; Agarwal, Deepak; Slade, Austen; Sahm, Erica; Large, Tim; Rivera, Marcelino
Abstract: Introductions: The American Society of Anesthesiologists Physical Status Classification System (ASA) is a validated risk stratification method for patients undergoing surgery. There is an increased prevalence of benign prostatic hyperplasia and comorbidities in our aging population. The role of ASA related to postoperative complications in patients undergoing holmium laser enucleation of the prostate (HoLEP) has not been described. Methods: A review of our database was performed for patients who underwent HoLEP from July 2018 to December 2020. Patients were stratified based on ASA score. Preoperative, perioperative, and complication data were analyzed using SAS analytics software. Results: Of 472 patients undergoing HoLEP, 320 (67.8%) were ASA 3–4 patients. There was a statistically significant difference found in age (72.3 ± 9.8 vs. 69.1 ± 9.0 years, p  < 0.001), body mass index (BMI) (29.0 ± 5.9 vs. 27.3 ± 4.2, p  = 0.004), and use of antiplatelet/anticoagulant medications (14.6% vs. 2.6%, p  < 0.001) in the ASA 3–4 group. There was no significant difference between prostate volume ( p  = 0.158) or catheter‐dependent urinary retention ( p  = 0.376). No difference was found in enucleation time (52.76 ± 24.8 vs. 54.16 ± 23.7 min, p  = 0.587), OR specimen weight (70.24 ± 58.5 vs. 81.53 ± 65.9, p  = 0.094). or intraoperative complications (2.8% vs. 1.3%, p  = 0.330). There were higher postoperative complications in the ASA 3–4 group (12.8% vs. 7.9%, p  = 0.03), but no difference in Clavien ≥3 complications ( p  = 0.068). ASA 3–4 patients had similar postoperative international prostate symptom score ( p  = 0.159). Conclusion: HoLEP is feasible and effective in patients who are ASA 3–4. The high‐risk cohort had an increased rate of low‐grade complications. Patients with an ASA score of 3–4 should be counseled regarding a higher rate of low‐grade complications.